The Effect of Madilog-Based Problem Based Learning Model on Elementary School Students' Critical Thinking Skills: A Study on Water Cycle Material - Bayu Wisesha; Aliet Noorhayati Sutisno; Nur Asyiah (FKIP - Universitas Riau, 2026)
Critical thinking is a core competency in 21st-century education. However, sociocultural trends may encourage students to approach problems without sufficient critical and rational thinking, including when learning objective phenomena such as the water cycle. This study examines the improvement of fifth-grade students’ critical thinking skills in the water cycle topic through Integrated Natural and Social Sciences (IPAS) instruction using a Problem-Based Learning model integrated with MADILOG (Materialism, Dialectics, Logic). A quantitative one-group pretest-posttest design was employed with 25 fifth-grade students at SDN 2 Sumber, Cirebon Regency, selected through total sampling. Data were collected using a validated and reliable essay test (r-count > 0.396; Cronbach’s Alpha = 0.767) covering six critical thinking indicators. The results showed an increase in students’ mean scores from 55.4 on the pretest to 84.0 on the posttest, with an N-Gain of 0.628 (62.76%), categorized as moderate. A paired-sample t-test showed a statistically significant increase in posttest scores. These findings indicate that PBL integrated with MADILOG may support the development of students’ critical thinking skills. Nevertheless, the one-group pre-experimental design, absence of a control group, and limited sample from one class and school restrict causal interpretation and broad generalization through future research and broader external validation.